O ensino da guitarra elétrica nos cursos de música da Universidade Federal da Paraíba: reflexões a partir de demandas discentes. - Dantas, Leonardo Meira (2015)
Nowadays musical education has taken part of a diversity of themes and points related to multiple contexts of music formation that constitute the contemporaneous society. In this universe the studies about popular music has gotten place and projections which shows singularities that is a part of the musician’s formation who will deal with this phenomenon. Inside of these studies has appeared a diversity of researches about teaching and learning the electric guitar, an instrument which has a strong insertion in the scene of the popular music since the middle of the 20th century. So, the purpose of this work is to comprehend the mainly demands of the learners from the UFPB Music Course and also in which ways they are engaged with the proposals and the musical pedagogical practice of these courses. The study was realized in the basis of an approaching qualitative research that observed collected data like bibliographical and documental researches, interviews, observations. Furthermore, it was used a questionnaire which is more suitable in quantitative researches, a fundamental tool to achieve the purposes of this work. From the results it is possible to affirm that the UFPB Guitar Courses give to the students new perspectives to perform and new discovering to continue and develop their practice like a musician. However it is clear that there is a big difference between the proposals of the pedagogical projects of the courses and the expectations and demands of the learners, not just this, the directed formation for the singularities of popular music and the electric guitar.